Earthly bodies, magical selves : contemporary pagans and the search for community - Pike, Sarah M., 1959- (University of California Press, 2001)
Recent decades have seen a revival of paganism, and every summer people gather across the United States to celebrate this increasingly popular religion. Sarah Pike's engrossing ethnography is the outcome of five years attending neo-pagan festivals, interviewing participants, and sometimes taking part in their ceremonies.